The Analysis Study of Underlying Disease, Symptoms and Mortality Rate of COVID-19: A Comprehensive Systematic Review - Anissa Paranoan; Anelsa Paranoan; Adeline Arung (International Medical Journal Corp. Ltd, 2025)
Background: The prevalence of underlying diseases in 22% of the global population increases their risk of severe COVID-19 outcomes. These conditions, often indicating a decline in physiological systems, compromise health and increase susceptibility to severe complications. A holistic approach is needed to understand their collective influence. Methods: This systematic review adhered to PRISMA 2020 guidelines, focusing exclusively on full-text articles published in English between 2014 and 2024. Editorials and review articles without a DOI were excluded to ensure the utilization of high-quality sources. A literature review was conducted utilizing reputable databases including ScienceDirect, PubMed, and SagePub to identify relevant studies. Result: The initial database search yielded approximately 1,300 publications relevant to the topic. Following a rigorous three-stage screening process, eight studies met the predefined inclusion criteria and were selected for in-depth analysis. Each study underwent a comprehensive critical evaluation, allowing for a detailed examination of the relationships between underlying diseases, symptoms, and COVID-19 mortality rates. This systematic approach ensured that the analysis was based on high-quality evidence, directly aligned with the study’s objectives, and contributed to a more precise and reliable understanding of the subject. Conclusion: The study highlights the impact of underlying diseases on COVID-19 outcomes, highlighting the need for proactive management strategies. The study also highlights the global trend in symptomatology and risk factors, emphasizing the need for region-specific healthcare policies. Understanding the interplay between diseases and outcomes is crucial for effective disease management.